Post stem cell transplantation revaccination: A survey of the current practices in India. Issue 16 (12th April 2018) - John, M. Joseph; Mathew, Amrith; Bhat, Sunil; Prabhakaran, Anushree; George, Biju; John, Jacob
Abstract: Background: Hematopoietic stem cell transplant (HSCT) recipients are more susceptible to infections from vaccine preventable diseases (VPDs) than the general population. Indian stem cell transplant registry (ISCTR) post-BMT vaccination guidelines were formulated in 2015. The objective of the survey was to assess the compliance to these guidelines among transplant physicians in India. Materials and methods: This is a cross-sectional survey executed as the quantitative research strategy to explore the various aspects of vaccination practices among transplant physicians in India. The 'data collection tool' included 36 predetermined questions related to vaccination of the patients and their close contacts. Theoretical construct of the questionnaire was face-validated and questionnaire survey forms were emailed individually as attachments or by google forms. This study is being reported based on the checklist for reporting results of internet e-surveys statement guidelines. Results: Survey forms were sent to 105 transplant physicians in India, 62% of whom responded representing 78.8% of transplant centers in India. More than 90% of allogeneic transplant physicians and 64% of autologous transplant physicians offered vaccination. Over two third of the physicians responded that they would discontinue vaccination at the onset of cGVHD. Fewer than one third physicians offered vaccination against Hepatitis A, Typhoid or Meningococcal infections. Forty two percent of respondents were unaware of the ISCTR post-BMT vaccination protocol. Only 47% of respondents reported complete adherence to any of the protocols they were following. Immune reconstitution to guide vaccination was available only to 13.3 percent of respondents. Conclusion: There is a need to improve the implementation strategies of vaccination in HSCT recipients to increase the adherence and continuation of it even in the presence of GVHD. There is also a need to extend the vaccination among VPDs especially prevalent in India.